Aneurysmal subarachnoid hemorrhage and severe, catheter-induced vasospasm associated with excessive consumption of a caffeinated energy drink. Issue 6 (December 2016) - Grant, Ryan A; Cord, Branden J; Kuzomunhu, Lovemore; Sheth, Kevin; Gilmore, Emily; Matouk, Charles C
Excessive consumption of over-the-counter stimulants is associated with coronary vasospasm, thrombotic complications, and sudden cardiac death. Their effects on cerebrovascular physiology are not yet described in the neurointerventional literature. Patients are increasingly exposed to high levels of these vasoactive substances in the form of caffeinated energy drinks and specialty coffees. We report a case of aneurysmal subarachnoid hemorrhage (SAH) and severe, catheter-induced vasospasm during attempted endovascular repair of a ruptured anterior communicating artery (AComA) aneurysm in the setting of excessive energy drink consumption. We review the literature and alert clinicians to this potentially serious complication.